Stress and coping - Perceptions of final year nursing students returning to clinical practice during the COVID-19 pandemic, South Africa - Mary Ann Jarvis; Penelope Martin; Margaret Williams; Fiona Walters; Olivia Baloyi; Jeffrey Hoffman; Jennifer Chipps (AOSIS, 2021)
Background: The novel nature of the coronavirus disease 2019 (COVID-19) pandemic places challenges on nursing students as they try to complete the clinical requirement of their training. Nursing faculties need to understand these challenges to support and equip nursing students to enter the workforce. Aim: To explore and describe the anticipated and subsequent perceptions of final year Bachelor of Nursing students returning to clinical practice during the COVID-19 pandemic in South Africa. Setting: The study was conducted at two universities in the Western Cape and KwaZulu-Natal, South Africa. Both universities offer 4-year Bachelor of Nursing programmes accredited by the South African Nursing Council and were in 'hot spot areas' for SARS-CoV-2. Methods: A qualitative study with focus groups discussions of final year undergraduate nursing students from both universities were conducted. Data were analysed through content analysis using Lazarus and Folkman's Stress Appraisal Coping Model. Results: Five focus groups discussions with a total of 25 participants were conducted. Three themes with eight sub-themes emerged, the key themes being: primary appraisal and anticipation of returning to clinical practice; contextual influence on primary appraisal and reappraisal to facilitate positive return to clinical practice. Conclusion: Primary perceptions of returning to clinical practice revolved around uncertainty and stress. However, through preparation and the process of reappraisal, participants were able to adapt and cope with the challenges in returning to clinical practice during the pandemic. Contribution: It is important to recognise the role of faculty in supporting nursing students' transition into situations of uncertainty such as the pandemic.